Incidence and Predictors of Clinical Outcomes in Real-Life Patients With Atrial Fibrillation Treated With Oral Factor Xa Inhibitors: The Follow-Up Results of the ANATOLIA-AF Study - Kocabas, Umut; Ergin, Isil; Sonmez, Sadi Can; Yavuz, Veysel; Murat, Selda; Ozdemir, Ibrahim Halil; Kivrak, Tarik (Wiley, 2025)
ObjectiveThe main objective of this study is to determine the incidence and predictors of clinical outcomes in patients with AF treated with factor Xa inhibitors in a real-world setting.MethodsThe present study was a multicentre and observational study that included patients with AF who were treated with factor Xa inhibitors. The primary outcome was the composite of ischemic stroke, TIA, systemic embolism, major bleeding, and all-cause mortality.ResultsA total of 1162 patients from 26 cardiology centers were included in this study, with a median age of 72 years. During the median 12-month follow-up period, the primary outcome occurred in 195 patients (16.8%). Treatment with rivaroxaban compared with apixaban and edoxaban showed a lower rate of ischemic stroke, TIA, and/or systemic embolism (2.2% vs. 4.7% vs. 6.5%, respectively, p = 0.014). The major bleeding rate was similar between all three factor Xa inhibitors. The all-cause mortality rate in the rivaroxaban group was lower compared with the apixaban and edoxaban groups (9.8% vs. 15.1% vs. 12.4%, respectively, p = 0.042). Overall, the frequency of primary outcome was 13.8%, 19.6%, and 20.6% for patients treated with rivaroxaban, apixaban, and edoxaban, respectively (p = 0.019). Older age, male sex, low body weight, high bleeding risk, heart failure, hypertension, liver failure, and treatment with apixaban 2.5 mg b.i.d. were independently associated with the development of primary outcome.ConclusionThe follow-up data from the ANATOLIA-AF study provides detailed data about the incidence and independent predictors of adverse clinical outcomes in patients with AF treated with factor Xa inhibitor treatment.
Keywords: atrial fibrillation; bleeding; factor Xa inhibitors; mortality; outcome; stroke